Gerakan Bahagia Bersama Tetangga (GBBT): Analisis Implementasi Distribusi Dana ZIS di Desa Pacar Peluk Kecamatan Megaluh Kabupaten Jombang - Hikmah, Salma Utiya; Choiri, Muttaqin (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2023)
Pacarpeluk is a village located in Megaluh District, Jombang Regency. The researcher is interested in analyzing the management of the ZIS distribution for one of the philanthropic activities that is also carried out by the girlfriends, namely the Happy Together with Neighbors Movement (GBBT). GBBT is a movement carried out in order to optimize the use of ZIS funds through active distribution from the community at the village level which in practice provides assistance during the month of Ramadan every year. This research is a descriptive qualitative research in which there are primary data obtained by means of interviews and direct observation and secondary data obtained from various literacy related to ZIS distribution management. The results of this study are that GBBT implements 4 management functions so that the distribution is well managed. The distribution of ZIS from the community to relatives in the same village has an impact that can be felt directly by the community from this movement, which has generated high interest from the community to continue giving donations and shadaqah through GBBT managers, considering that GBBT's income has increased 3 times in just 1 year.